Childhood Deaths Due to Firearm Injuries in Izmir and Nearby Cities - Aydın, Faruk; Yavuz, Mehmet Sunay (The Bulletin of Legal Medicine, 2020)
Introduction: Childhood deaths due to the firearm injuries are rising in our country and worldwide. In this study, our aim was to examine the deaths related to firearm injuries in an age group 18 and under, in İzmir and neighboring provinces between 01.01.2006 and 31.12.2015 and the information such as sociodemographic aspects, the types of the firearms, origin, region of injury, place of death, shooting distance, and the owner of the firearm.Materials and Methods: In our study, autopsy report and forensic investigation files of 1.876 firearm injuries in and around İzmir were retrospectively reviewed and 114 (6,07%) of these cases were referred as deaths of 18 years old or younger. The data were evaluated using SPSS version 22 program. Percentage, ratio and chi-square statistics were used in the data analysis.Results: The ages of the cases varied from one to 18, 79 (69,3%) of the cases were male, mean age is 14,04 ± 4,23, and male / female ratio was 2,25. Guns and shotguns were used in 39 cases (34,2%) and in 75 cases (65,8%) respectively. When the cases were evaluated corresponding to their origins; homicide was the first with 37 cases (32,5%). It was found that deaths occurred most frequently in winter (n: 32, 28,1%). Most of the cases occurred in rural areas such as villages and towns (n=48, 42,1%) and the incidence mostly took place within houses (n=54, 47,4%). In 35 cases (30,7%) the owner of the weapon was the father of the victim.Discussion and Conclusion:...
Keywords: Child, Firearm, Death, Forensic Autopsy